2010
DOI: 10.1111/j.1872-034x.2010.00740.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of short‐term dexamethasone therapy in acute‐on‐chronic pre‐liver failure

Abstract: Five-day dexamethasone therapy is effective in improving the liver function and survival rate of patients with pre-ACLF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 25 publications
3
44
0
Order By: Relevance
“…Whatever the mechanism of AE, a few weeks are needed for sufficient suppression of the production of HBV-related proteins by preventing HBV replication even when NAs are used [40]. Thus, earlier introduction of CS in combination with potent antiviral therapy is a reasonable approach for the initial treatment of AE to prevent excessive immunological reactions and progression of liver cell injury [22,41]. NA or CS used on its own has limits in the resolution of the serious conditions.…”
Section: Discussionmentioning
confidence: 98%
“…Whatever the mechanism of AE, a few weeks are needed for sufficient suppression of the production of HBV-related proteins by preventing HBV replication even when NAs are used [40]. Thus, earlier introduction of CS in combination with potent antiviral therapy is a reasonable approach for the initial treatment of AE to prevent excessive immunological reactions and progression of liver cell injury [22,41]. NA or CS used on its own has limits in the resolution of the serious conditions.…”
Section: Discussionmentioning
confidence: 98%
“…Corticosteroids have several other hepatoprotective roles, including preventing cytolysis of ballooned hepatocytes and protecting hepatocytes against apoptosis induced by cadmium toxicity (12)(13)(14). Previous work by the present authors and other groups has revealed that corticosteroids are effective in treating pre-acute-on-chronic liver failure (pre-ACLF) associated with HBV and severe acute exacerbation (SAE) of chronic hepatitis B (15)(16)(17). Therefore, treating ALF and SALF with corticosteroids is a reasonable treatment regimen.…”
Section: Introductionmentioning
confidence: 93%
“…All articles discussed the effect of glucocorticoid on the survival rate. Five studies discussed the effect of glucocorticoids on TBIL [24,[26][27][28][29]. Four studies discussed the effect of glucocorticoid on PTA [24,[26][27][28].…”
Section: Description Of Trialsmentioning
confidence: 99%
“…The design and results of the two studies were available in their abstract. Four studies [3,[27][28][29] focused on preliver failure and four [24][25][26]30] examined liver failure. All studies compared glucocorticoid therapy with routine medical treatment and observation occurred for more than 4 weeks.…”
Section: Description Of Trialsmentioning
confidence: 99%
See 1 more Smart Citation